THE LEGAL PROTECTION OF PREGNANT WORKERS AND WORKING MOTHERS ACCORDING TO TURKISH LABOUR LAW - Tuaç, Pelin (International Journal of Contemporary Economics and Administrative Sciences, 2018)
The number of women that participated in the labour market is increasing with every passing day. Besides, the request to control one's own individual preferences and also the amount of time is emerging. Thus, to raise their children employees have recess to their occupation or they want to have short time working. In this context, the new regulations brought to working life that get out of traditional approach, has become to ensure harmony in work and family life. After the women took place as workers, the necessity of protecting the women in the worklife became important. The protection was firstly held by the international regulations. Regulations have been enacted to prevent the gender discrimination. These regulations contain provisions on various measures such as income inequality, the limitation of working hours, and types of work, which are not suitable for the female workers. Turkish Constitution states that the men and female workers have the equal rights, however the woman workers are granted by special rights in terms of working conditions. Maternity in working life was reflected to the regulations also as motherhood; pregnancy and confinement. Each of these cases has led to the different regulations should be made for women in working life. All these processes are effective in women's recruitment, the organization of work, working conditions and termination of the employment contracts. The author discusses the harmonization of the Turkish Labour Code No. 4857 and the further related legislation in Turkey to the international legislation. In conclusion, the author points out the fact that, the Turkish and international legislation have already been successfully harmonized to a wide extent, whereas the development of the legal practice in the same way has failed.